Association of siblings' presence and oral health-related quality of life among children: a cross-sectional study - Min Liu; Qingping Yun; Mei Zhao; Wei Chen; Hui Zhang; Wei Hou; Chun Chang (BMC, 2021)
Abstract Background The quantity-quality trade-off theory indicates that an increase in siblings might decrease a child's well-being, but little is known about the impacts of sibling number on children's oral health-related quality of life (OHRQoL). This study aims to investigate the effects of presence of siblings on children's OHRQoL, and to further test whether there is an interaction effect between siblings' presence and locations on children's OHRQoL. Methods Data were obtained from an oral-health survey of 12-year-old children in Beijing, China, which was a part of the 4th National Oral Health Survey in the Mainland of China (2015-2016). This study included 2158 children data for analysis. OHRQoL was assessed by the child's Oral Impacts on Daily Performance (OIDP). OIDP prevalence served as an indicator of OHRQoL. Children with and without siblings were recorded as non-single and single children, respectively. Dental variables, including active caries, gingival bleeding, and calculus, were reported. A logistic regression model was applied to investigate the association of siblings' presence and OIDP prevalence. A synergy index was used to assess the possible interaction effect between siblings' presence and location on OIDP prevalence. Results Sixty percent of Chinese children reported suffering OIDP in the previous six months. OIDP prevalence for non-single and single children were 68.3% and 56.9%, respectively. The adjusted odds ratio (OR) of OIDP for non-single children was 1.31 (95% CI: 1.05, 1.63), and the adjusted OR of OIDP for non-single and rural children was 2.03 (95% CI: 1.47, 2.81). The synergy index between siblings' presence and location on OIDP was 2.18 (85% CI: 1.30, 3.67), which indicates that an excessive risk increase for OIDP was observed among non-single and rural children. Conclusions Children with siblings are more likely to report OIDP and have lower OHRQoL, especially those from rural areas. These findings indicate that oral-health interventions should be given priority for non-single and rural children.